Zoneamento ambiental acÚstico como estratÉgia de gestÃo e controle da poluiÇÃo sonora Urbana - Bressane, Adriano [UNESP]; Mochizuki, Patricia Satie; Caram, Rosana Maria; Roveda, José Arnaldo Frutuoso [UNESP] (My University, 2015)
Its impacts transformed noise pollution in one of the most severe forms of environmental degradation. However, considering the constant urban and demographic growing, with respective increase and densification of noise sources, control actions become so complex, as urgent. In this context, the aim of this study was to develop a methodology to the acoustic zoning as control strategy, integrated territorial planning, applied as study case in Rio Claro city, São Paulo State, Brazil. For that, law guidelines and literature references on strategic noise mapping, constituted the main materials used. Thus, were proposed standards and acoustic zones associated with typology of land use, protection of sensitive establishments and prevention of neighborhood conflicts. As a results of application in the study area, was obtained sensitive to noise zones, destined for: protection of urban biodiversity (21.0 km2); maintenance of healthy conditions in residential areas, schools and hospitals (8.3 km2); installation of trade, services and industrial not annoying (10.3 km2); exposure prevention of residents, workers and consumers in areas with mixed use (11.2 km2); territorial conditions and extensions necessary for the development of noisy activities (9.9 km2). Therefore, we conclude that the procedure proposed to acoustic environmental zoning can contribute to advancement of solutions for the control of noise pollution, collaborating to achieve healthy and sustainable cities.
Acoustic environmental zoning as strategy of management and control of the urban noise pollution
Keywords: Land use; Strategic cartography; Urban noise